Unit operations handbook - McKetta, John J. (Marcel Dekker, 1993)
Emphasizes the design, control, and functioning of various unit operations - offering shortcut methods of calculation along with computer and nomographic solution techniques. Provides practical sections on conversion to and from SI units and cost indexes for quick updating of all cost information.;This book should be of interest to mechanical, chemical, process design, project, and materials engineers and continuing-education courses in these disciplines.